Near‐Infrared Small Molecule Acceptor Enabled High‐Performance Nonfullerene Polymer Solar Cells with Over 13% Efficiency. (14th June 2018) - Gao, Wei; Liu, Tao; Ming, Ruijie; Luo, Zhenghui; Wu, Kailong; Zhang, Lin; Xin, Jingming; Xie, Dongjun; Zhang, Guangye; Ma, Wei; Yan, He; Yang, Chuluo
Abstract: One of the most promising approaches to achieve high‐performance polymer solar cells (PSCs) is to develop nonfullerene small molecule acceptors (SMAs) with an absorption extending to the near‐infrared (NIR) region. In this work, two novel SMAs, namely, BTTIC and BTOIC, are designed and synthesized, with optical bandgaps ( E g opt ) of 1.47 and 1.39 eV, respectively. Desipte the narrow E g opt, the PBDB‐T:BTTIC‐ and PBDB‐T:BTOIC‐based PSCs can maintain high V OC s of over 0.90 and 0.86 V, respectively, with low energy losses ( E loss ) < 0.6 eV. Meanwhile, due to the favorable morphology of the PBDB‐T:BTTIC blend, balanced carrier mobilities are achieved. The high external quantum efficiencies enable a high power conversion efficiency (PCE) up to 13.18% for the PBDB‐T:BTTIC‐based PSCs. In comparison, BTOIC shows an excessive crystallization propensity owing to its oxyalkyl side groups, which eventually leads to a relatively low PCE for the PBDB‐T:BTOIC‐based PSCs. Overall, this work provides insights into the design of novel NIR‐absorbing SMAs for nonfullerene PSCs. Abstract : Two near‐infrared (NIR) small molecule acceptors (SMAs) with different side groups, namely, BTTIC and BTOIC, are designed and synthesized. PBDB‐T:BTTIC‐based polymer solar cells (PSCs) achieve power conversion efficiency of up to 13.18%, which is significantly higher than that of PBDB‐T:BTOIC‐based PSCs. The result shows that the alkylthienyl is superior to oxyalkyl and huge potential of NIR SMAs.